浮き趾の有る子どもと無い子どもの足裏形態及び足趾筋力の比較 - 出村, 愼一; 浮田, 咲子 (発育発達研究, 2019)
Floating toes have been a suspected cause of falls and are thought to affect foot form and exertion of toe muscle strength. This study examined foot form and toe muscle strength in children with and without floating toes. The subjects were 372 boys and girls aged 5-10 years old. We measured their height, weight, toe muscle strength, foot length, foot width, heel width, center of gravity position, and the internal and external arches of both feet. Floating toes were found in 17.4％ of the boys and 10.9％ of the girls and occurred most frequently with the fifth toe in both sexes. No significant differences in age, physique, toe muscle strength, or foot form were found in the groups with and without floating toes, suggesting that floating toes are neither related to foot form nor to toe muscle strength.